Analisis Faktor Yang Berhubungan Perilaku Hidup Bersih dan Sehat (PHBS) di Wilayah Kerja Puskesmas Bandar Agung Kabupaten Musi Banyuasin Tahun 2021 - Wulandari, Ria; Romadhon, Muhammad; Mustakim, Mustakim (JURNAL KESEHATAN TERAPAN, 2022)
and vegetables: 73%, for daily physical activities: 87%. The purpose of this study was to examine the relationship between predisposing factors (knowledge), enabling factors (clean water facilities, healthy latrines, trash cans) and reinforcing factors (community culture, support from health workers and community leaders) with the implementation of PHBS in the community. Methods: This research is quantitative in nature using an analytical survey method with a Cross Sectional approach. A sample of 52 people was selected using the cluster random sampling method. The independent variables of this study are knowledge, clean water facilities, healthy latrines, trash cans, community culture, support from health workers and community leaders, while the dependent variable is clean and healthy living behavior. The data is then processed using SPSS to see if there is a relationship between the variables studied. Results: The results of the research on the support variable of community leaders obtained a p value of 0.636 (0.05) meaning that there was no relationship between the support of community leaders for PHBS. Conclusion: One of the factors that has an important role in clean and healthy living behavior is family knowledge. Keywords: PHBS.